Influence of Project Management Practices on Performance of Projects in Rwanda - Iribagiza, Alice; Kirabo, Joyce (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: This research aimed to assess how project management aspects, specifically project risk control, planning, and monitoring and evaluation processes, impact the performance of USAID-sponsored projects in Rwanda. The study focused on the CORE project in Rubavu District, supported by USAID and the Rwanda Governance Board. Methodology: A descriptive research design was employed, targeting 170 individuals involved in the CORE project. A sample size of 119 participants was determined using Yamane’s simplified formula, with purposive and stratified sampling methods ensuring a representative selection. Data were collected using a combination of questionnaires and an interview guide, including both closed and open-ended questions. The reliability of the instruments was ensured through test-retest and input from a university supervisor. Internal consistency was confirmed using Cronbach’s alpha, with a reliability coefficient of 0.7 or above considered acceptable. Data were analyzed using SPSS software, and inferential analysis and multiple regression were employed to determine the significance of each variable. Findings: The study achieved a 92.4% response rate, with a higher proportion of male (50.9%) and degree-holding participants (50.9%). Findings revealed that project risk management (Mean = 3.9108) had the greatest impact on project performance, followed by project planning (Mean = 3.9545) and monitoring and evaluation (Mean = 3.7369). These factors were found to significantly influence project success. Unique Contribution to Theory, Practice and Policy: The research recommends strategies to strengthen adherence to effective monitoring and evaluation processes, particularly focusing on improving risk management and planning practices to enhance project performance in USAID-sponsored initiatives.